Quality of life and emotional impact of a fixed‐dose combination of antihypertensive drugs in patients with uncontrolled hypertension. Issue 2 (27th October 2016) - Schmieder, Roland E.; Jumar, Agnes; Fronk, Eva‐Maria; Alexandre, Ana‐Filipa; Bramlage, Peter
Abstract : Often considered to be a symptomless condition, hypertension can be associated with a significant emotional burden. To analyze changes of health‐related quality of life as well as the emotional burden questions regarding the impact of hypertension were incorporated into the noninterventional SeviTarget study. Comparisons were made between baseline and follow‐up findings, and between patients with treatment target achievement and those without. A total of 5831 patients were recruited. At baseline, only 33.3% of patients described their current state of health as good or excellent, while at follow‐up this value had risen to 75.8%. Responses regarding symptoms and limitations in activities and mental factors such as anxiety associated with treatment all improved during antihypertensive treatment. Changes to more optimistic responses were more likely for patients who achieved a target BP of <140/90 mm Hg. The study demonstrates that improvements in quality of life and the perceived emotional burden related to hypertension can be achieved with effective management of hypertension.